2020
DOI: 10.1111/josh.12974
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Weight Perceptions and Electronic Bullying on Suicide‐Related Risk Behaviors among Youth: Results from Youth Risk Behavior Surveillance System, 2015

Abstract: BACKGROUND: For youth between the ages of 10 and 24, suicide is the third leading cause of death, and results in approximately 4600 lives lost each year. Body weight status and bullying is associated with increase mental health disorders. METHODS: We analyzed data from the 2015 Youth Risk Behavior Survey, consisting of 15,506 students in grades 9-12. Logistic regression analysis was performed using STATA13 to estimate the independent association of perceived weight status and bullying experienced at school and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Suicidal thoughts were also more likely among participants trying to lose weight than those who were not trying to lose weight. This study supports and adds to the previous research that has documented consistent suicidality themes for older adolescents with body dissatisfaction and weight loss intentions [52][53][54] by demonstrating the same relationship among younger adolescents. Including prevention programming in schools that addresses the influence of media on the body has been documented to promote body satisfaction, self-esteem, and increase awareness of unrealistic body types due to photoshop.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Suicidal thoughts were also more likely among participants trying to lose weight than those who were not trying to lose weight. This study supports and adds to the previous research that has documented consistent suicidality themes for older adolescents with body dissatisfaction and weight loss intentions [52][53][54] by demonstrating the same relationship among younger adolescents. Including prevention programming in schools that addresses the influence of media on the body has been documented to promote body satisfaction, self-esteem, and increase awareness of unrealistic body types due to photoshop.…”
Section: Discussionsupporting
confidence: 86%
“…52 Another study using national YRBS high school data found that considering or attempting suicide was associated with perceiving oneself to be very/slightly over or underweight, while making a suicide plan was associated with perceiving oneself to be slightly/very overweight and injuring oneself while attempting suicide was associated with perceiving oneself to be very over or underweight. 53 A third study also using national YRBS high school data found that body image and weight control behaviors, among other factors, were significant predictors of suicidal behaviors. 54 Although there are fewer studies about suicidality and body dissatisfaction for middle schoolers, 1 study using the YRBS for Kentucky middle school students found that those with both disordered eating behaviors and suicidality were more likely to engage in a number of risk behaviors including cigarette, alcohol, and prescription drug use.…”
Section: Suicidal Ideation and Body Dissatisfactionmentioning
confidence: 99%
“… 35 The pressure from trying to actualise this idealised body weight by the adolescents and young people increased their vulnerability to low self-esteem, suicidal behaviour and other mental illness. 35 , 36 College staff screening for abnormal body weight perception and other risk factors of suicide attempts can be utilised to identify students that need further assessment and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Past researchers using data from the YRBS have reported that suicidality in high school students is associated with female sex ( 2 , 4 ), sexual minority status ( 47 49 ), adverse childhood experiences ( 50 , 51 ), physical teen dating violence ( 52 ), forced sexual intercourse ( 18 , 53 ), body weight perceptions [both overweight ( 54 , 55 ) and underweight ( 55 )], illicit drug use ( 13 , 18 ), prescription opioid misuse ( 56 58 ) [especially in girls ( 59 )], alcohol use ( 15 , 18 , 60 , 61 ), marijuana use ( 13 , 15 , 62 ), bullying ( 18 , 55 , 63 , 64 ) and cyberbullying ( 18 , 55 , 63 65 ), frequent physical fighting ( 66 ), excessive television/video game/internet use ( 67 , 68 ), insufficient sleep ( 69 ), and even soft drink consumption ( 70 ). With so many variables being associated with suicidality in youth—especially given the very large national sample allowing the identification of statistically significant findings with small effect sizes—it is not particularly surprising that concussion was also associated in the present study, in univariate analyses, and in prior studies using the 2013 ( 45 ) and 2017 YRBS ( 41 43 , 46 ).…”
Section: Discussionmentioning
confidence: 99%